The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0188579
|View full text |Cite
|
Sign up to set email alerts
|

Efficient enhancement of information in the prefrontal cortex during the presence of reward predicting stimuli

Abstract: The prefrontal cortex (PFC) is a key brain structure for decision making, behavioural flexibility and working memory. Neurons in PFC encode relevant stimuli through changes in their firing rate, although the metabolic cost of spiking activity puts strong constrains to neural codes based on firing rate modulation. Thus, how PFC neural populations code relevant information in an efficient way is not clearly understood. To address this issue we made single unit recordings in the PFC of rats performing a GO/NOGO d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In a recent study (Mininni et al . 20 ), we found that the coding capacity in PFC increases efficiently during stimuli presentation in a Go/NoGO discrimination task. Further theoretical considerations suggest that changes in PFC signal-to-noise correlation ratio induced by VTA dopamine neurons could explain our results.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…In a recent study (Mininni et al . 20 ), we found that the coding capacity in PFC increases efficiently during stimuli presentation in a Go/NoGO discrimination task. Further theoretical considerations suggest that changes in PFC signal-to-noise correlation ratio induced by VTA dopamine neurons could explain our results.…”
Section: Introductionmentioning
confidence: 70%
“…Given that PFC neurons may code information by either increasing or decreasing their firing rate, we employed mutual information (MI) as a measure of information content in PFC to estimate the amount of information conveyed by neural activity regardless of the direction of firing rate changes. To this end, we first built a two-state neuron model that allowed a reliable estimation of MI 20 . In the model, we set the output of every neuron to ‘0’ or ‘1’ depending on whether the number of spikes within a given time window was lower/higher than the average computed in the same window across all correct GO and NoGO trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical procedures were performed as previously described 28 . Rats were deeply anesthetized with a single I.P.…”
Section: Methodsmentioning
confidence: 99%